Evaluation of Different Rates of NPS on Growth and Yield Performances of Garlic (Allium sativum L.) in Cheha District, Gurage Zone, Ethiopia - Bewuket Gashaw (International Journal of Agronomy)
A field experiment was conducted on 2019 growing season to evaluate effects of different rates of nitrogen, phosphorus, and sulfur on growth and yield of garlic under supplemental irrigation. A local variety, Tuma, was used and treated with six rates of NPS (T1 (0 : 0 : 0 kg/ha NPS) (control), T2 (19 : 38 : 7 kg/ha NPS), T3 (28.5 : 57 : 10.5 kg/ha NPS), T4 (47.5 : 76 : 14 kg/ha NPS), T5 (47.5 : 95 : 17.5 kg/ha NPS), and T6 (57 : 114 : 21 kg/ha NPS)). The experiment was laid out in randomized complete block design and replicated three times. Data were collected for days to 50% emergence, plant height, leaf number, leaf length, bulb weight, and total bulb yield. SAS version 9.2 was used to analyze the data. Means were separated using Fisher’s test at 5% level of significance. All parameters were significantly P<0.05 affected by the rates of NPS. The early days to 50% emergence (16) was recorded from T6 (57 : 114 : 21 kg/ha NPS), whereas the late days to 50% emergence was recorded from the control treatment (T1). Significantly highest leaf length (41.51 cm), leaf number (13.63), plant height (61.19 cm), bulb weight (39.44 g), and total bulb yield (14.91 ton ha−1) were recorded from T6 (57 : 114 : 21 kg/ha NPS). Therefore, from the result of this study, it can be concluded that the maximum total bulb yield of garlic was obtained with the application of 57 : 114 : 21 kg/ha NPS rate.